Embryo Quality: The Most Critical Factor for Pregnancy Rates after day-2, day-3, and day-5 of Embryo Transfer - Tono Djuwantono (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To determine the most critical factor on day-2, day-3, and day-5 of embryo transfer in correlation with pregnancy rates. Method: This research is a retrospective study in Aster Fertility Clinic, IVF program- Dr. Hasan Sadikin Hospital, Bandung, Indonesia. One hundred ninety five women enrolled in an IVF program conducted from March 2006 through November 2009 at the Aster Fertility Clinic. Effect of embryo-transfer day and any other factors (including quality of embryo, oocyte quantity, difficulty of embryo transfer technique, and blood or mucus contamination on the catheter) on pregnancy rate in IVF. Results: The mean age of the pregnant group was 34.65 (SD = 3.91), and the mean of the infertility period was 7.25 years (SD = 3.54). There were no siginificant differences in pregnancy rates in the day-2, day-3, and day-5 groups. The most critical factor influencing pregnancy was the total score for the quality of embryos [p = 0.001; OR (CI 95%) = 1.94 (0.91 - 4.08)]. Otherwise, the day of embryo transfer, oocyte quantity, and difficulties in embryo transfer did not affect the pregnancy rate (p > 0.05). Conclusion: Our study suggests that the total score for the quality of the embryos was the most critical factor for the success rate of pregnancy rather than the day of embryo transfer, oocyte quantity, difficulty of embryo transfer technique, or contamination of blood and mucus on the catheter. [Indones J Obstet Gynecol 2010; 34-4: 175-9] Keywords: day of embryo transfer, in vitro fertilization, quality of embryo total score, oocytes quantity, catheter contamination